Comparison of Void Fraction on Annular and Churn Two-Phase Flow Patterns in Mini Pipe with a Slope of 15° Against Horizontal Position. Issue 1 (February 2021) - Sukamta,; Sudarja,; Sundari, Sri
Abstract: The two-phase flow is part of a multiphase flow, where the flow can consist of gas/vapor and liquid phases, which flow simultaneously. This study aims to compare the characteristics of void fraction values in the annular and churn flow patterns that can be known from the parameters of the gas and liquid superficial velocity, the length of the flow pattern, and the frequency of the flow pattern. But, in this study, the focus is on the superficial velocity of both gas and liquid. Tests were carried out on mini pipes with a diameter of 1.6 mm and a length of 160 mm with a slope of 15° to the horizontal position. Working fluid used was air and water mixed with glycerin with a concentration of 40%, 50%, 60%, 70%. Analysis of research results using the probability distribution function analysis with the help of Matlab and Microsoft Excel programs. The results showed that the comparison of the value of the void fraction of the annular and churn flow patterns was significantly influenced by several factors, namely the superficial velocity of the gas, the superficial velocity of the liquid, and the viscosity of the liquid. The higher the superficial velocity of the gas, the higher the value of the void fraction, so it tends to cause the annular flow pattern. And vice versa, the higher the superficial liquid velocity, the smaller the void fraction value will be and make the condition irregular, causing the churn flow pattern.